Merencanakan Pemecahan Masalah Kontekstual: Berpandu pada Rumus atau Konteks? - Ani, Suki Isffi; Rosyidi, Abdul Haris (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2021)
This study aims to analyze the planning process for solving contextual problems. The research subjects consisted of three students of class IX SMP. The research used is a qualitative research with a descriptive approach. The instrument used is a task-based interview. The data is analyzed according to the indicators of problem solving at the planning stage, namely identifying information, selecting old knowledge that can be used in problem solving, mentioning theorems related to the problem, making plans. The results showed that the first student was able to identify the information needed but the student did not submit it in writing. The first student solved the problem using the volume formula, but the student experienced a conceptual error in the middle of completion. The second student is able to identify and write down the required information, the second student uses mathematical formulas and estimates to determine the amount of wrapping paper needed. The third student is able to understand which information can be used and which information is redundant. At first the third student used the formula to solve the problem, but in the middle of the completion the student changed the plan by applying real life/context applications. Based on the results of research conducted that two students out of three students when solving problems did not pay attention to the context.